Effectiveness of a Time-limited Incentive on Participation by Hard-to-reach Respondents in a Panel Study. Issue 3 (August 2017) - Fomby, Paula; Sastry, Narayan; McGonagle, Katherine A.
We describe an experiment to provide a time-limited incentive among a random sample of 594 hard-to-reach respondents, 200 of whom were offered the incentive to complete all survey components of a study during a three-week winter holiday period. Sample members were primary caregivers of children included in the 2014 Child Development Supplement to the U.S. Panel Study of Income Dynamics. The incentive provided US50 to caregivers who completed a 75-minute telephone interview and whose eligible children each completed a 30-minute interview. Results indicate that the incentive was an effective and cost-efficient strategy to increase short-term response rates with hard-to-reach respondents and had no negative impact on final response rates.